LEGAL BASIS FOR INTERSTATE COOPERATION IN CONDITIONS OF SANCTION PRESSURE - Kudryavsev Igor Vladimirovich.,; Kostin Sergey Andreyevich,; Kurbanov Jahongir Abdimutalliyevich, (Лучшие интеллектуальные исследования, 2024)
Annotation: this article was co-authored, and according to it, the meaning of sanctions in the national legal system and the application of sanctions in international law and the name of the countries where sanctions are applied in the international arena are highlighted. Also, the history of sanctions and the purpose of their application are given.